(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 1999)
The aim of the text is to investigate Benjamin’s critique to the romantic notion of allegory and its relationship with the role of language in Schopenhauer’s philosophy, mainly concerning about the exclusion of language from aesthetics.